Barvni vid - Mohorič, Aleš (Obzornik za matematiko in fiziko, 2015)
The article describes human color vision, basics of color systems and a way of repre- senting color of a light with a given spectrum by readily available software.
Keywords: človeški vid; oko; barvni sistemi; Arbeidsgiverforeningen Spekter; spekter